1999
DOI: 10.1152/jappl.1999.86.4.1347
|View full text |Cite
|
Sign up to set email alerts
|

Tomographical description of tennis-loaded radius: reciprocal relation between bone size and volumetric BMD

Abstract: Effects of long-term tennis loading on volumetric bone mineral density (vBMD) and geometric properties of playing-arm radius were examined. Paired forearms of 16 tennis players (10 women) and 12 healthy controls (7 women), aged 18-24 yr, were scanned at mid and distal site by using peripheral quantitative computerized tomography. Tomographic data at midradius showed that tennis playing led to a slight decrease in cortical vBMD (-0.8% vs. nonplaying arm, P < 0. 05) and increase both in periosteal and endocoritc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
50
4

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(65 citation statements)
references
References 23 publications
11
50
4
Order By: Relevance
“…In fact, when the absolute values of the cortical and trabecular densities were compared, they seemed to be virtually constant between players and controls, and across the bone sites, except the distal radius. This finding is similar to other CT studies where the volumetric density of cortical and trabecular bone has been shown to be fairly similar between children at different ages, and between men and women, 2,[15][16][17]36 and where the higher areal bone mineral density and ultimate bone strength in older children and men were due to larger bone size, not volumetric density of bone. In contrast to our study, Rico et al 33 found a significantly larger total and cortical volumetric density, but not trabecular density of the dominant distal radius, compared with the nondominant counterpart of sedentary right-handed adult subjects.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In fact, when the absolute values of the cortical and trabecular densities were compared, they seemed to be virtually constant between players and controls, and across the bone sites, except the distal radius. This finding is similar to other CT studies where the volumetric density of cortical and trabecular bone has been shown to be fairly similar between children at different ages, and between men and women, 2,[15][16][17]36 and where the higher areal bone mineral density and ultimate bone strength in older children and men were due to larger bone size, not volumetric density of bone. In contrast to our study, Rico et al 33 found a significantly larger total and cortical volumetric density, but not trabecular density of the dominant distal radius, compared with the nondominant counterpart of sedentary right-handed adult subjects.…”
Section: Discussionsupporting
confidence: 90%
“…In the present study, all our players started their playing careers during childhood and significant enlargements in bone geometry, without changes in volumetric density, were observed. Interestingly, in a recent pQCT study of the radius of tennis players, Ashizawa et al 2 showed that three players who had not started playing until the age of 16 seemed to have higher trabecular bone density, but similar cross-sectional area of the distal radius. This may suggest a compensatory mechanism of mature bone in response to mechanical loading.…”
Section: Discussionmentioning
confidence: 99%
“…(6,7,30,32,33) In our study, PA was not associated with cortical density in any of the groups. This characteristic seems to be an inherent feature of cortical density as regards the influence of exercise.…”
Section: Calcium Intake Physical Activity and Bonecontrasting
confidence: 61%
“…The significant increase in Ct.Dn at the diaphyseal sites (14, 38 and 66%) is in contrast to cross-sectional studies reporting no differences in volumetric Ct.Dn between athletic populations and controls [21,23] or between the playing and contralateral limb in tennis players [44]. Changes in Ct.Dn have not been demonstrated with short exercise interventions [38] or long-term participation in high impact sports [23].…”
Section: Discussionmentioning
confidence: 99%